2018
DOI: 10.1002/jtr.2177
|View full text |Cite
|
Sign up to set email alerts
|

Towards an improved typology approach to segmenting cultural tourists

Abstract: This study aims to improve the cultural tourist typology methodology that uses cultural centrality and depth of cultural experience in its framework. Using a sample of Chinese tourists in Macau (n = 595) collected via questionnaire surveys, the study confirmed the determination effect of cultural centrality on depth of cultural experience. Subsequently, the study demonstrated an improved approach that eliminates such a determination effect in typology identification. Compared to McKercher's () approach, the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
0
21
0
4
Order By: Relevance
“…There are several studies that evidence that women prefer these cultural places (Vong & Ung, 2012;Nguyen & Cheung, 2014;Remoaldo et al, 2014;Ramires et al, 2017). On the other hand, there are also studies that show the contrary and conclude that men are the ones who are most attracted to these destinations (Correia et al, 2013;Antón et al, 2017;Chen & Huang, 2017;Hall, 2017). Controversy is also present in relation to another of the variables analyzed in this type of studies: age.…”
Section: Segmentationmentioning
confidence: 96%
See 1 more Smart Citation
“…There are several studies that evidence that women prefer these cultural places (Vong & Ung, 2012;Nguyen & Cheung, 2014;Remoaldo et al, 2014;Ramires et al, 2017). On the other hand, there are also studies that show the contrary and conclude that men are the ones who are most attracted to these destinations (Correia et al, 2013;Antón et al, 2017;Chen & Huang, 2017;Hall, 2017). Controversy is also present in relation to another of the variables analyzed in this type of studies: age.…”
Section: Segmentationmentioning
confidence: 96%
“…Thus, empirical evidence indicates quite different age brackets. For example, Chen and Huang (2017) identify tourists between 21 and 35 years old; Anton et al (2017) find ages between 30 and 44 years; Remoaldo et al (2014) identify ages that range from 26 to 45; Huh, Uysal and McCleary (2006) show ages that range between 38 and 47 years; and Correia et al (2013) and Ramires et al (2017) establish ages over 45 years. In relation to the level of training, the existing academic literature indicates that visitors who go to destinations where an artistic and monumental heritage predominates have a certain level of university academic training.…”
Section: Segmentationmentioning
confidence: 99%
“…Among the main factors that are the object of study, visitor age is one of the most recurrent. Most investigations conclude that cultural tourists tend to be young or middle-aged (below 45 years), or even between 21 and 35 years [31]. On the other hand, some scholars increase this age profile to between 26 and 45 years [6] or 30-44 years [21].…”
Section: Visitors' Socio-economic Characteristicsmentioning
confidence: 99%
“…In terms of educational level of tourists visiting heritage destinations, most research has found that this type of tourist general has completed higher education [9,10,21,30,32,33], although it remains important to highlight the attractiveness of destinations with an important cultural and natural heritage among university students [31].…”
Section: Visitors' Socio-economic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation